Distribution Characteristics of Swirling-Straight Sprinklers Inside a Nuclear Power Pressurizer - Jinghao Bi; Xiao Xu (Energies)
Droplet size and distribution uniformity of sprinklers significantly affect production safety in the processes of steam temperature and pressure reduction within nuclear power, and other high-temperature, high-pressure industries. In industrial sprays with high flow rates and low pressure drops, reducing droplet size poses additional challenges, making improved spray uniformity essential for enhancing heat transfer. This study designed and produced a set of swirling-straight sprinklers, tested their flow characteristics and liquid distribution, and proposed a highly uniform spray mode involving swirl jet interaction mixing. The discharge coefficient (Cd) changes indicated that enlarging the jet channel area diminishes the amplification effect, suggesting a trade-off in industrial high flow sprinkler design. A detailed evaluation and analysis method of the spray process, which is superior to the use of a single uniformity parameter, is proposed based on Gaussian function peak fitting method. It has been observed that the relationship between the Gaussian fitting parameters and the pressure drop of the sprinkler tends to be linear. This discovery provides a new basis for designing nozzles with low pressure drop, high flow rates, and uniform distribution. The findings contribute to the optimization of spray performance and provide valuable data for computational fluid dynamics model verification.